Design of a switched capacitor DC-DC converter for sensor node - Ang, Jer Shuan (Nanyang Technological University, 2023)
In this work, a Switched Capacitor DC-DC Converter with Pulse Skip Modulation dedicated to energy harvesting system in wireless sensor node application is presented. The design is implemented in the 55nm CMOS technology. Converter topology used in this work is a 5-stage Dickson Charge Pump driven by a non-overlapping clock signal of 1.2V and 1MHz realized by a ring oscillator. Pulse Skip modulation block consists of a comparator with hysteresis of 24mV and a voltage reference that can provide 564mV at 26°C with a temperature coefficient of 10.34ppm/°C. The overall system can provide a 2.5V output voltage with a cold-start input power of -20dBm at 0.2V. The circuit design is can also provide an output current of 20mA for 3ns per 3 minutes. Pertaining to the output current consumption, the output voltage drop of the design is limited to be within 70mV.